On immunity : an inoculation - Biss, Eula (Graywolf Press, 2014)
Upon becoming a new mother, Eula Biss addresses a chronic condition of fear: fear of the government, the medical establishment, and what is in children's food, mattresses, medicines, and vaccines. Biss investigates the metaphors and myths surrounding the conception of immunity and its implications for the individual and the social body. As she hears more and more fears about vaccines, Biss researches what they mean for her own child, her immediate community, America, and the world.